Malnutrition among older adults living in Portuguese nursing homes: The PEN-3S study - Madeira, T (2019)
ObjectiveTo characterise the nutritional status and to identify malnutrition-associated variables of older adults living in Portuguese nursing homes.DesignCross-sectional study. Data on demographic and socio-economic characteristics, self-reported morbidity, eating-related problems, nutritional status, cognitive function, depression symptoms, loneliness feelings and functional status were collected by trained nutritionists through a computer-assisted face-to-face structured interview followed by standardised anthropometric measurements. Logistic regression was used to identify factors associated with being at risk of malnutrition/malnourished.SettingPortuguese nursing homes.SubjectsNationally representative sample of the Portuguese population aged 65 years or over living in nursing homes.ResultsA total of 1186 individuals (mean age 83·4 years; 72·8 % women) accepted to participate. According to the Mini Nutritional Assessment, 4·8 (95 % CI 3·2, 7·3) % were identified as malnourished and 38·7 (95 % CI 33·5, 44·2) % were at risk of malnutrition. These percentages increased with age and were significantly higher for women. Logistic regression showed (OR; 95 % CI) that older adults reporting no or little appetite (6·5; 2·7, 15·3), those revealing symptoms of depression (2·6; 1·6, 4·2) and those who were more dependent in their daily living activities (4·7; 2·0, 11·1) were also at higher odds of being malnourished or at risk of malnutrition.ConclusionsMalnutrition and risk of malnutrition are prevalent among nursing home residents in Portugal. It is crucial to routinely screen for nutritional disorders, as well as risk factors such as symptoms of depression and lower functional status, to prevent and treat malnutrition. Copyright (c) The Authors 2018.